1990
DOI: 10.1007/bf00706118
|View full text |Cite
|
Sign up to set email alerts
|

Family characteristics of preschool social competence among black children in a Head Start program

Abstract: Social competence has been suggested to serve a protective function in emotional functioning and may compensate for some deleterious experiences. This study found that adherence to family routines and older fathers were significant predictors of preschool social competence. The subjects were 91 black children enrolled in a metropolitan Head Start program who were rated for social competence by their teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 27 publications
2
36
1
Order By: Relevance
“…These parenting strategies have been shown to be important for both majority and minority families (Brody & Flor, 1997;Jackson, et aI., 2000;Keltner, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These parenting strategies have been shown to be important for both majority and minority families (Brody & Flor, 1997;Jackson, et aI., 2000;Keltner, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of AfricanAmerican preschoolers, Keltner (1990) found increased cooperation and compliance associated with reports of increased family routines. In a similar correlational study with children between 6 and 9 years of age, Brody and Flor (1997) found that home environments with more family routines were associated with reduced internalizing behaviors.…”
Section: Parental Structure: Family Routines In African-american Famimentioning
confidence: 97%
See 3 more Smart Citations